IMPACT OF SYSTEMATIC TRAINING IN EMOTIONAL INTELLIGENCE ON THE SECONDARY SCHOOL TEACHERS’ EQ LEVELS - Suryawanshi, Arati (PEOPLE: International Journal of Social Sciences, 2017)
Introduction: While working with various educational institutes and being a trusty of family school, researcher had to deal with all the issues related with Teachers’ training, recruitment, and teaching learning processes. Researcher was also teaching in the renowned college at Mumbai, and after that, working as Psychological and Emotional Intelligence consultant at a very big Educational Organization in Mumbai. Researcher got an opportunity to have a dialogue with various principals and management trusties and educationists and the people working in human resource departments of Educational Institutes. She found that all are agreed with the fact that all the teachers are Intelligent and some of them are Brilliant to bring the subject to students, given them to teach. But they also mentioned that, the most of the times the whole teaching learning process is becoming very stressful and that is transferred to students as well. Some teachers are trying very hard to make it interesting but that is not enough. That motivated the researcher to discover what must be there beneath the whole process. At the same time, she also had to deal with many cases of the teachers who have come to her to resolve their issues and she found that it’s not their Intelligence but it’s their emotions intervening in the process, they are intelligent but most of them don’t know how to deal with their emotions in their personal life, at work or at social level that is somewhere interfering in the process. So the aim of the research is to find out their Emotional Intelligence levels and also then after training in Emotional Intelligence, with post assessments, finding out whether there is any significant change. Objective: While working on the Ph.D. thesis, one of the aims of the researcher is to discover, “The impact of the systematic training in emotional intelligence on the overall competencies of emotional intelligence levels of teachers.”Methodology: To understand the impact on teachers, the “Social Emotional Intelligence Assessment” was conducted for secondary school teachers teaching in two CBSE (Central Board of School Education) Schools in the periphery of Nasik District, Maharashtra, India. Research was conducted for the teachers of both the schools. Training in Emotional Intelligence was conducted for the teachers of one school, where as teachers of other school were gaining EQ with the knowledge they had and the knowledge they acquired with the reports of their assessments provided to them. The training modules involved emotional intelligence skills such as, empathy, how the teacher can live with a purpose, navigating emotions and recognizing patterns. All the modules were uniquely designed and developed by the Researcher herself. Findings: The teachers who participated in the training programs showed almost 14% rise in various competencies of Emotional Intelligence. Research Outcomes: The teachers mentioned that the whole process is changing and bringing a lot of positivity, hope and ease and interest among classrooms, students and in their lives as well. Their life is changing at all levels as at personal level, at work, Social and family level.Future Scope: This research has been conducted in two C.B.S.E schools; in future it can be conducted in many other syllabus also for working staff in the organizations, or in the states other than Maharashtra.